EV-Mediated Chemoresistance in the Tumor Microenvironment: Is NF-κB a Player? - Di Vito Nolfi, Mauro; Vecchiotti, Davide; Flati, Irene; Verzella, Daniela; Di Padova, Monica; Alesse, Edoardo; Capece, Daria; Zazzeroni, Francesca (Frontiers in Oncology, 2022)
Drug resistance is a major impediment to patient survival and remains the primary cause of unsuccessful cancer therapy. Drug resistance occurs in many tumors and is frequently induced by chemotherapy which triggers a defensive response both in cancerous and cancer-associated cells that constitute the tumor microenvironment (TME). Cell to cell communication within the TME is often mediated by extracellular vesicles (EVs) which carry specific tumor-promoting factors able to activate survival pathways and immune escape mechanisms, thus sustaining tumor progression and therapy resistance. NF-κB has been recognized as a crucial player in this context. NF-κB activation is involved in EVs release and EVs, in turn, can trigger NF-κB pathway activation in specific contexts, based on secreting cytotype and their specific delivered cargo. In this review, we discuss the role of NF-κB/EVs interplay that sustain chemoresistance in the TME by focusing on the molecular mechanisms that underlie inflammation, EVs release, and acquired drug resistance.